Identification and optimization of a novel series of indoleamine 2, 3-dioxygenase inhibitors. Issue 3 (1st February 2017) - Markwalder, Jay A.; Seitz, Steven P.; Blat, Yuval; Elkin, Lisa; Hunt, John T.; Pabalan, Jonathan G.; Jure-Kunkel, Maria N.; Vite, Gregory D.; Covello, Kelly
Graphical abstract: Abstract: The discovery of a series of structurally-novel biaryl urea IDO inhibitors is described. Optimization of a micromolar hit through iterative cycles of synthesis and screening in an assay measuring IDO-mediated intracellular conversion of tryptophan to kynurenine led to potent inhibitors with favorable selectivity and metabolic stability profiles.